2012
DOI: 10.1016/j.carbon.2011.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen storage in CO2-activated amorphous nanofibers and their monoliths

Abstract: Amorphous carbon nanofibers (CNFs), produced by the polymer blend technique, are activated by CO 2 (ACNFs). Monoliths are synthesized from the precursor and from some ACNFs. Morphology and textural properties of these materials are studied. When compared with other activating agents (steam and alkaline hydroxides), CO 2 activation renders suitable yields and, contrarily to most other precursors, turns out to be advantageous for developing and controlling their narrow microporosity (< 0.7 nm), V DR (CO 2 ). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Surprisingly, OB‐CO 2 sample has outperformed nanoporous materials with higher specific surface area , which reveals that surface area is not the only parameter that needs to be regarded. Even though, many investigators have shown that, at 77K and subatmospheic pressures, the hydrogen uptake was governed by the microporosity and the specific surface area of the tested adsorbents . Actually, the only exceptional feature of OB‐CO 2 sample is its ultramicroporous character, with a well ordered pore system centered at 0.65 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, OB‐CO 2 sample has outperformed nanoporous materials with higher specific surface area , which reveals that surface area is not the only parameter that needs to be regarded. Even though, many investigators have shown that, at 77K and subatmospheic pressures, the hydrogen uptake was governed by the microporosity and the specific surface area of the tested adsorbents . Actually, the only exceptional feature of OB‐CO 2 sample is its ultramicroporous character, with a well ordered pore system centered at 0.65 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Although hydrogen adsorption in ACs at ambient temperature is relatively low even at high pressures [3e5] due to the low quadrupole moment and the low polarizability of the H 2 molecule [4], hydrogen cryosorption is considered to be a promising method for hydrogen storage, as ACs can reversibly adsorb substantial quantities of hydrogen with fast adsorption/ desorption kinetics [6,7]. The porous texture is the main feature determining the hydrogen adsorption capacity of ACs.…”
Section: Introductionmentioning
confidence: 99%
“…Porous materials like activated or templated carbons [1][2][3][4], metal-organic frameworks (MOFs) [5,6], covalent organic frameworks (COFs) [7], etc. are interesting candidates for gas storage application [8][9][10].…”
Section: Introductionmentioning
confidence: 99%